2019
DOI: 10.1200/jco.2019.37.15_suppl.6562
|View full text |Cite
|
Sign up to set email alerts
|

Access to care and financial burden for patients with breast cancer in Ghana, Kenya, and Nigeria.

Abstract: 6562 Background: Breast cancer is the most frequently diagnosed malignancy and the most common cause of cancer-related death in women in Ghana, Kenya, and Nigeria. We evaluated healthcare resource use and financial burden for patients treated at tertiary cancer centers in these countries. Methods: Records of breast cancer patients treated at the following government/private tertiary centers were included – Ghana: Korle-Bu Teaching Hospital and Sweden Ghana Medical Centre; Kenya: Kenyatta National Hospital and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Limited access to these main forms of therapy has been described for SSA, 12 linked to both geographic and financial inaccessibility, with most women having to pay out-of-pocket for healthcare. 13,14 In this study, surgery was the most available therapy option, with 64.2% of women in the traced cohort having a record of surgery. Still, many women never received surgery because of either inoperable or stage IV disease, fear of disfigurement, lack of access to surgery, or options to use neoadjuvant chemotherapy.…”
Section: Main Findings In the Context Of Previous Studiesmentioning
confidence: 78%
“…Limited access to these main forms of therapy has been described for SSA, 12 linked to both geographic and financial inaccessibility, with most women having to pay out-of-pocket for healthcare. 13,14 In this study, surgery was the most available therapy option, with 64.2% of women in the traced cohort having a record of surgery. Still, many women never received surgery because of either inoperable or stage IV disease, fear of disfigurement, lack of access to surgery, or options to use neoadjuvant chemotherapy.…”
Section: Main Findings In the Context Of Previous Studiesmentioning
confidence: 78%
“…With these financial challenges faced by these women, they had to rely on family members, employers and other people for assistance to enable them go through treatment. A lot of studies have reported similar findings (Sanuade et al, 2018;Twahir et al, 2019;White-Means, Dapremont, Davis, & Thompson, 2020). Amid the financial difficulties, some employers promised to assist some participants with payment of hospital bills;…”
Section: Discussionmentioning
confidence: 85%
“…The high cost of breast cancer treatments as reported in the study supports several similar findings from different context including low‐ and middle‐income countries (Ekwueme & Trogdon, 2016; Pisu et al., 2017). Currently, financing cancer treatment in Ghana comes as the sole responsibility of the individual patients and the treatment begins with a series of diagnostic investigations that are typically financed out of pocket payment (Twahir et al., 2019; Vanderpuye et al., 2017). Furthermore, the three available treatment strategies: chemotherapy, surgical interventions and radiotherapy are associated with exorbitant costs over a long period (Vanderpuye et al., 2017).…”
Section: Discussionmentioning
confidence: 99%
“…With the high level of poverty in Nigeria, most patients still bear the full cost of their breast cancer screening/diagnosis and treatment from out of pocket indicating that only the privileged may be able to afford cancer care. 19 Provision of electronic online support group system may increase the number of willing patients and help to reduce attrition rate.…”
Section: Discussionmentioning
confidence: 99%